Regulasi Diri dan Kecemasan Berbicara di Depan Umum pada Mahasiswa - Larasati, Chatarina Lintang; Sari, Diana Permata (Universitas Mercu Buana, 2024)
Public speaking anxiety is a fear for many people, and college students are no exception. This study aims to determine the relationship between self-regulation and public speaking anxiety in college students. This type of research is a correlational quantitative research. The research hypothesis proposed is that self-regulation has a significantly negative relationship with public speaking anxiety. Respondents in this study were 150 students aged 18-25 years. The measuring instrument used in this study is a translation of the Short Self-Regulation Questionnaire scale compiled by Pichardo et al. (2013) (14 items, r = 0.852) and a modification of the Personal Report Public Speaking Anxiety scale compiled by Mortberg et al. (2018) (17 items, r = 0.909). The results showed that the hypothesis proposed by the researcher was accepted, namely that there is a significant negative relationship between self-regulation and public speaking anxiety in college students (r = -0.455; with p = 0.000). Based on these results, students who are be able to regulate themselves well, could overcome public speaking anxiety.